Effect of Fuzheng Qingdu Therapy for Metastatic Gastric Cancer is Associated With Improved Survival: A Multicenter Propensity-Matched Study. (November 2021) - Hou, Chao; Yang, Die; Zhang, Yusen; Li, Yifei; He, Zhengfei; Dai, Xiaojun; Lu, Qingyun; Wang, Shanshan; Zhang, Xiaochun; Liu, Yanqing
Objective: To evaluate the therapeutic effect of Traditional Chinese Medicine (TCM), specifically Fuzheng Qingdu (FZQD) therapy, on the survival time of metastatic GC patients. Patients and Methods: Databases of medical records of 6 hospitals showed that 432 patients with stage IV GC were enrolled from March 1, 2012 to October 31, 2020. Propensity score matching (PSM) was used to reduce the bias caused by confounding factors in the comparison between the TCM and the non-TCM users. We used a Cox multivariate regression model to compare the hazard ratio (HR) value for mortality risk, and Kaplan-Meier survival curve for the survival time of GC patients Results: The same number of subjects from the non-TCM group were matched with 122 TCM-treated patients after PSM to evaluate their overall survival (OS) and progression-free survival (PFS). Median time of OS of TCM and non-TCM users were 16.53 and 9.10 months, respectively. TCM and non-TCM groups demonstrated a 1-year survival rate of 68.5% and 34.5%, 2-year survival rate of 28.6% and 3.5%, and 3-year survival rate of 17.8% and 0.0%, respectively. A statistical difference exists in OS between the 2 groups (χ 2  = 33.39 and P  < .0001). The PFS of TCM users was also longer than that of non-TCM users (χ 2  = 4.95 and P  = 0.026). Notably, Chinese herbal decoction, Shenmai and compound Kushen injections were commonly used for FZQD therapy. Conclusion: This propensity-matched study showed that FZQD therapy could improve the survival of metastatic GC patients.